Rancang Bangun Aplikasi Evaluasi Kinerja Alat Harbour Mobile Crane Berbasis Web Pada PT. Berlian Jasa Terminal Indonesia - Rachman, Bobby; Setyawan, Henry Bambang; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: PT Berlian Jasa Terminal Indonesia (PT BJTI) is a subsidiary of PT Pelabuhan Indonesia III (Persero). As agencies engaged in the field of port, PT BJTI apply timeliness in reporting and recording daily conduct HMC operational tool, PT BJTI often have inaccuracies in recording daily reports HMC operational tool, it makes the results of the evaluation to be late, so the decision to become a HMC tool operation not in time, and reporting systems that are not effectively make HMC operational reporting process becomes longer because the recording is done in the field and then submitted to the office (staff) at a considerable distance.Through the analysis, it is known that the delay reporting conducted field operators resulting length HMC tool performance evaluation conducted by Supervisor Equipment II that became the target suitability report is not timely. Of problems and analysis of existing problems, it is necessary that the application can perform a performance evaluation of web-based tools that HMC is built based on interviews and observations that have been made. Based on the results of testing and evaluation, it is known that the application can provide detailed information about HMC performance reporting tool, so that the evaluation can be done on time and not until there is delay in the provision of monthly reports and statements report the suitability of the target.